Communication Strategy of the Education Office and the Serang City Health Office on the Issue of Food Health for School Children (PJAS) in Improving Food Safety - Mulyasih, Rahmi; Mujtaba , Burhanudin; Winangsih, Rahmi; Sagita, Darwis (Future Science, 2025)
The issue of healthy snacks for school children (PJAS) is an issue that highlights the consumption of healthy food for school children. This arises because there are cases of food poisoning that occur in several areas caused by poor food quality selection in the end causing poisoning for school children. Therefore, a communication strategy is needed in order to provide comprehensive knowledge about healthy snacks for school children which is of concern not only to the school, but also food sellers and parents of students. The Health Office and the Education Office have made several efforts to provide an understanding of healthy snacks for school children in collaboration with other agencies such as BPOM. With the cooperation carried out between cross-work units in Serang City, it is hoped that cases of food poisoning for school children will not occur again.